Barriers and facilitators for individualized rehabilitation during breast cancer treatment - a focus group study exploring health care professionals' experiences - Ulrika Olsson Möller; Ing-Marie Olsson; Katarina Sjövall; Ingela Beck; Lisa Rydén; Marlene Malmström (BMC, 2020)
Abstract Background Breast cancer (BC) and related treatment are associated with the risk of developing a wide range of persistent disabling impairments. Despite extensive research in the field and an enhanced focus on BC rehabilitation, up to 34-43% of these patients are at risk of developing chronic distress. In addition, it is known that these patients repeatedly report unmet needs, which are strongly associated with reduced quality of life. However, despite knowledge that patients' needs for support during BC rehabilitation varies greatly, individualized rehabilitation is often lacking. Therefore, this study aimed to explore health care professionals' (HCPs) experiences of current rehabilitation practice and describe current barriers and facilitators for individualized rehabilitation for patients following BC treatment. Methods A total of 19 HCPs were included, representing various professions in BC care/rehabilitation within surgical, oncological and specialized cancer rehabilitation units at a university hospital in Sweden. Five semi structured focus group interviews were conducted and inductively analysed using conventional qualitative content analysis. Results Three categories were captured: (1) varying attitudes towards rehabilitation; (2) incongruence in how to identify and meet rehabilitation needs and (3) suboptimal collaboration during cancer treatment. The results showed a lack of consensus in how to optimize individualized rehabilitation. It also illuminated facilitators for individualized rehabilitation in terms of extensive competence related to long-term experience of working with patients with BC care/rehabilitation. Further, the analysis exposed barriers such as a great complexity in promoting individualized rehabilitation in a medically and treatment-driven health care system, which lacked structure and knowledge, and overarching collaboration for rehabilitation. Conclusion This study suggests that the cancer trajectory is medically and treatment-driven and that rehabilitation plays a marginal role in today's BC trajectory. It also reveals that structures for systematic screening for needs, evidence-based guidelines for individualized rehabilitation interventions and structures for referring patients for advanced rehabilitation are lacking. To enable optimal and individualized recovery for BC patients', rehabilitation needs to be an integrated part of the cancer trajectory and run in parallel with diagnostics and treatment.